Administration of Acacia (Acacia mangium) Leaves Ethanol Extract Cream 5% Prevented The Increase of Melanin Number in Ultraviolet B-Exposed Guinea Pig (Cavia Porcellus) Skin - Olivia Julita; Ida Sri Iswari; Anak Agung Gede Putra Wiraguna (IJAAM (Indonesian Journal of Anti-Aging Medicine), 2020)
Introduction: Ultraviolet exposure stimulate oxidative stress-mediated melanogenesis, which is the sign of photoaged skin. Acacia (Acacia mangium) leaves extract contains high levels of antioxidants. The aim of this study was to prove the effectiveness of the Acacia leaves ethanol extract cream in preventing an increase of melanin. Methods: This experimental study used randomized posttest only control group design. The research subjects were 36 male guinea pigs (Cavia porcellus), healthy, local strains, aged 3 months, weighing 300-350 grams and had never received prior treatment. Subjects were divided into 2 groups (18 individuals each), namely the control group (treatment with ultraviolet B exposure and basic cream) and the treatment group (treatment with ultraviolet B exposure and acacia leaves ethanol extract cream 5%). After 2 weeks of treatment, the amount of melanin was examined histopathologically using Masson-Fontana staining. Results: The average number of melanin in the control group was 19.33±2.59% while in the treatment group was 2.21±1.25%. Comparative analysis using independent t-test showed that the value of p<0.001. Conclusion: This study suggesting that administration of acacia (Acacia mangium) leaves ethanol extract cream 5% prevented increasing amount of melanin in ultraviolet B-exposed guinea pig (Cavia porcellus) skin. The results showed that there was number of melanin in the control group (19.33±2.59%) were higher than the treatment group (2.21±1.25%) (P<0.001).